The Interlanguage Pragmatics of Greetings - Shleykina, Galina (Widya Mandala Catholic University Surabaya, 2019)
The present study centers on interlanguage and cross-cultural pragmatics. It investigates semantic formulas in the speech act of greeting performed by Russian EFL learners. In particular, it compares the non-native speakers’ (NNS) and native speakers’ (NS) production of semantic formulas in terms of number, frequency, and content. A Free Discourse Completion Test (FDCT) containing 16 situational prompts elicited greetings by the English NNSs and NSs. The results show that the NNSs significantly deviate from the NSs in terms of number, frequency, and content of greetings strategies, namely, greetings proper, phatic questions and phrases, address terms, and situational greetings. The differences result from negative pragmalinguistic and sociopragmatic transfer, lack of appropriate linguistic means, or not fully developed pragmatic competence. Important pedagogical implications regarding pragmatic instruction are discussed. The results contribute to a better understanding of how EFL learners greet and respond to greetings. They also shed light on the discussion of L2 learners’ pragmatic competence and appropriateness.